(untitled) (Ustozlar uchun, 2025)
Collocations, the habitual combinations of words, play a significant role in language fluency and translation. Theoretical perspectives from lexical semantics, phraseology, and cognitive linguistics explain their nature. However, translators often face challenges due to language-specific collocations, cultural nuances, and syntactic differences. This study investigates these theoretical aspects and translation-related problems, analyzing practical examples from English-Uzbek translation to propose effective strategies for improving translation quality.